Emotional and Spiritual Determinants of Tourist Attachment in Halal Destinations: Evidence from Netnographic Investigation of Online Reviews - Indira Rahma Annisa; Azhar Alam; Arina Saputri; Raisa Aribatul Hamidah (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2026)
This study advances extant literature through the application of a qualitative netnography methodology, utilising Google Reviews as a data source to investigate the manner in which dimensions of tourist attachment to halal destinations influence revisit intention. A corpus of 766 reviews was collected from Indonesia's ten foremost halal tourism destinations, from which 165 reviews meeting relevance criteria were subjected to thematic coding and analysis. The findings demonstrate that tourist attachment to halal destinations is constituted through several salient dimensions, namely tranquility and serenity, sentiments of comfort and belonging, cognitive and educational stimulation, and appreciation of sharia-compliant facility provision. These dimensions of attachment are found to precipitate revisit intention via expressions of longing, affirmative recommendation behaviour, and destination admiration. From a managerial perspective, the results underscore the necessity of augmenting worship facilities and halal infrastructure, cultivating an ambience conducive to visitor tranquillity and comfort, and formulating destination marketing strategies that foreground the emotional and spiritual dimensions of the tourism experience.